Analysis of the Quality of Inpatient Health Services at Medan Haji General Hospital - Yusuf Hanafi Lubis; M Dwi Setiawan; Fennisyah Andriani Saragih; Ellisha Putriady; Widya Oktaviani; Fani Dwi Yanti; Mira Ulpayani Harahap; Rahmi Atika; Putra Apriadi Siregar (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2022)
Currently the hospital is innovating to increase the level of patient satisfaction indicators which are still a problem in the quality of health services. The purpose of this research is to raise issues related to the quality of inpatient services at RSU Haji Medan. The method used is descriptive analytic with a cross-sectional study design, namely through a sample of 189 people taken from 9818 populations through calculations using a categorical descriptive formula and drawn by purposive sampling, data collection is carried out based on direct interviews using a questionnaire instrument adopted from RISKESNAS Ministry of Health of the Republic Indonesia, after the survey was conducted, the data were analyzed by means of frequency and central distribution, statistical tests using the Spearman rho correlation, multiple linear regression. The results showed that the average patient was still in the dissatisfied category (mean = 150.79), the Spearman rho test stated that there was a relationship of all variables with the quality of inpatient health services p <0.05 with the highest correlation direction of 0.540 in the fairly strong category , Partially patient satisfaction has a value of t = 3.442 and has a coefficient value of 0.201, if there is an increase in patient satisfaction of 0.1%, the quality of inpatient health services will improve by 20.1%. This study concludes that constantly at 13.6% and simultaneously (F=34.835) influences the quality of inpatient health services, leaders and health human resources work together to build even better health services to improve service quality. Keywords: Correlation, Hospital, Linear, Quality, Service